2006
DOI: 10.1158/1078-0432.ccr-05-2530
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib Up-Regulates the Expression of the ζ Chain of T Cell Receptor Complex in Tumor-Infiltrating Lymphocytes in Human Cervical Cancer

Abstract: + TIL as well as in tryptase-positive cells. IL-12 levels were significantly reduced in posttreatment samples with respect to baseline levels (P = 0.002). We also found a reduction in the circulating levels of vascular endothelial growth factor, and a statistically significant increase of serum endostatin levels (P = 0.035). Conclusions: We reported the first evidence in humans that celecoxib restores~expression by TIL in primary cervical tumors, suggesting that a positive modulation of immune function may ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…However, whether lower doses of celecoxib are sufficient or not to maximally inhibit COX-2 activity is unknown: on the basis of our results, the dose of 400 mg/day can be considered clinically as adequate to the main purpose of chemosensitization. One can argue that we did not find in the sera of our patients any modulation of key angiogenesis-related factors, such as the pro-angiogenic VEGF and the anti-angiogenic endostatin, which have been previously associated with the antitumoral activity of celecoxib given at doses of 800 mg/day [16,38]. However, while higher doses are required to obtain antitumoral effects with celecoxib alone in terms of short-term modulation of molecular markers involved in tumor growth, apoptosis, immune function or angiogenesis [16], these could not be necessary for circumventing COX-2-mediated chemoresistance mechanisms in combinational study with chemotherapy.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, whether lower doses of celecoxib are sufficient or not to maximally inhibit COX-2 activity is unknown: on the basis of our results, the dose of 400 mg/day can be considered clinically as adequate to the main purpose of chemosensitization. One can argue that we did not find in the sera of our patients any modulation of key angiogenesis-related factors, such as the pro-angiogenic VEGF and the anti-angiogenic endostatin, which have been previously associated with the antitumoral activity of celecoxib given at doses of 800 mg/day [16,38]. However, while higher doses are required to obtain antitumoral effects with celecoxib alone in terms of short-term modulation of molecular markers involved in tumor growth, apoptosis, immune function or angiogenesis [16], these could not be necessary for circumventing COX-2-mediated chemoresistance mechanisms in combinational study with chemotherapy.…”
Section: Discussionmentioning
confidence: 95%
“…All samples were aliquoted and stored at -80°C until assay. Serum levels of vascular endothelial growth factor (VEGF) and endostatin were measured by a solid phase chemiluminescent ELISA assay (R&D Systems, Abingdon, United Kingdom), according to the manufacturer's protocol [16]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased expression of CD3 zeta chain in human cancer was reviewed by Whiteside [34]. Interestingly, patients with cervical cancer after successful chemotherapy showed a restoration of zeta chain-expressing T cells [35]. Therefore, a decrease of CD3 zeta chain-expression in malignant cancer processes is reversible.…”
Section: Discussionmentioning
confidence: 99%
“…Zehbe et al [16] studied cervical intraepithelial lesions CIN I (n=3), CIN III (n=7), invasive cervical carcinoma (CC) (n=13) and normal cervical tissue (n=5) and evaluated for T-cell receptor zeta chain immunohistochemistry, found that reduced T-cell receptor zeta chain expression is not necessarily linked to a chronic viral infection, or to the presence of transformed cells, but rather to the stromal invasion of the cancer lesion. Ferrandina et al [17] found celecoxib up-regulates the expression of the zeta chain of T-cell receptor complex in tumor-infiltrating lymphocytes in human cervical cancer. Using expression microarray analysis, Watson et al [18] revealed ACTG2 genes may be associated with cisplatin resistance to breast cancer cell.…”
Section: Tab 3 Identification Of Protein Spots By Mass Spectrometrymentioning
confidence: 99%